FRA JOURNALIST TIL „BIG MAMMA“: Om sociale rollers betydning for antropologers datagenerering - Hasse, Cathrine (Tidsskriftet Antropologi, 1995)
Cathrine Hasse: From Journalist to „big mamma“. On the Meaning of Social Roles in Anthropological Data Generation The article takes up the question of the different social roles the anthropologist utilizes in the field, the interchange between the field and the anthropologist’s personal social equipment, and how this can be used to get data from selected groups of informants. As an example of this approach the author describes how she herself went from being „ journalist", which frightened her informants, to the much more socially accepted role as „ig mamma“, which opened for a more emotional relationship between herself and the people in the small Sardinian village, Mamoiada, where the fieldwork took place.